PENENTUAN UMUR PANEN BEBERAPA GENOTIPE PADI (Oryza sativa L.) BERDASARKAN SATUAN PANAS PADA SISTEM BUDIDAYA ORGANIK DAN NON ORGANIK - Putri, Della Alvia Kusuma; Dulbari, Dulbari; Sudrajat, Denny; Subarjo, Subarjo; Jaya, Moh. Haris Imron S. (JURNAL AGROTROPIKA, 2025)
Determining the harvest time of rice plants is one of the determining factors for the success of rice production. Calculation of harvest time can be done using the heat unit method. This study aims to calculate the accumulation of heat units of several rice genotypes (Oryza sativa L.) in organic and non-organic cultivation systems. This study was conducted in September-December 2023 at Polinela Organic Farm (POF), Lampung State Polytechnic (5°21'10"S 105°13'43"E, 114 m above sea level using a Randomized Complate Block Design (RCBD) with four rice genotypes (PTP 01, Inpari 24, Jaliteng, and Pandan Wangi), which were planted in two different cultivation systems and replicated three times. The results showed that the four rice genotypes used showed significant differences in the accumulation of heat units between organic and non-organic cultivation systems. Organic cultivation systems require a higher average heat unit (1193.1°C days) than non-organic systems (1146.3°C days). Organic cultivation systems provide more stable growth in grain weight per panicle, the number of filled grains per panicle, and fewer empty grains. This demonstrates the importance of genotype selection and cultivation system in optimizing production and harvest time.